Does Freedom Matter for Growth? Analysing Patterns of Association with Cross Country data using Causality and Classification Techniques - M, Arvind; P, Sarika; M G, Deepika; G, Sangeetha (International Journal of Engineering and Technology, 2018)
Why have some countries experienced high growth and why are some lagging behind has always been a matter of debate in economic literature. The traditional theories of growth have looked at many factors including labour, capital and technology which were at the centre of analysis of growth models. There was yet another line of reasoning which debated on how economic freedom could be an influencing factor on economic growth. Given the access to the latest data on economic freedom and its components from Heritage Foundation, we attempt to establish the nature of empirical relationship between economic freedom and growth.We run the Ordinary Least square multiple regression model to test the causal relationship between freedom and growth and use cluster analysis, a classification tool to test for association with the chosen variables. Results of the regression model did not reveal a strong causal relationship between freedom and growth. However, cluster analysis shows strong association of GDP percapita with that of economic freedom and its components highlighting that economic freedom could be an important factor influencing growth and prosperity of nations in the long run but may not be sufficiently influencing in the short run.Â